An Overview Study of Low Back Pain Event Among the Dentist in Yogyakarta - Arya Adiningrat; Damian Abdul (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2020)
Introduction: Low back pain is a pain sensation in spinal and paraspinal structure of lumbosacral region. The prevalence of low back pain event in several country show the significant percentage every year. Dentist is a high-risk profession related to musculoskeletal disorders particularly low back pain. Bad posture, static sitting position and repetition movement are several risks possibility for the occurrence of low back pain. Objective: This research is purposed to evaluate the prevalence overview of low back pain event among the dentist in Yogyakarta city. Methode: This research was designed by the descriptive observational approach using cross sectional research design. The samples were 76 dentists under the “Indonesian Dentist Association of Yogyakarta” region. The research was conducted through questionnaires utilization to measure the level of low back pain from the respondents to the no disabillity, minimal disabillity, moderate disabillity dan severe disability categories. Result: The result showed that among dentist population in Yogyakarta there were 37 dentists (49%) suffered low back pain with no disabillity, 35 dentists (46%) low back pain with minimal disabillity and 4 dentists (5%) low back pain with moderate disabillitywhile there were nodentist suffered from low back pain with severe disabillity (0%). Conclusion: The total prevalence of low back pain event among dentist in Yogyakarya city categorized by all the severity level was 39 dentists (or 51%) suffered from a low back pain of musculoskeletal disorder.